Adjunctive ablation strategies improve the efficacy of pulmonary vein isolation in non-paroxysmal atrial fibrillation: a systematic review and meta-analysis. (4th March 2017) - Afzal, Muhammad R.; Samanta, Anweshan; Chatta, Jawaria; Ansari, Brihh; Atherton, Sam; Sabzwari, Syed; Turagam, Mohit; Lakkireddy, Dhanunjaya; Houmsse, Mahmoud
ABSTRACT: Background : Pulmonary vein (PV) isolation (PVI) has suboptimal outcomes in patients with non-paroxysmal atrial fibrillation (AF). Adjunctive strategies employed to ablate non-PV triggers have shown favorable outcomes. Aims : To delineate the incremental benefit of adjunctive ablation in patients with non-paroxysmal AF through a meta-analysis. Methods and results : Database searches through August 2016 identified five non-randomized and seven randomized controlled trials (enrolling 1694 patients). The adjunctive strategies employed for non-PV ablation included focal impulse and rotor modulation; empirical linear lines, ablation of complex fractionated atrial electrograms and ganglionated plexi. The risk ratio (RR) for AF recurrence, calculated with random effects meta-analysis showed a 36% reduction of AF recurrence at a median follow up of 12 months (RR: 0.64, 95% Confidence interval: 0.48 to 0.85; p = 0.003). The benefits persisted during longer follow up when assessed in subgroup analysis. Conclusions : Addition of adjunctive ablation to PVI improves outcomes.